Assessment of Wood Properties of Hevea brasiliensis Clones Grown in Zamboanga Sibugay Philippines for their Potential Applications: 10.32526/ennrj/24/20250060 - Marasigan, Oliver S.; Alipon, Marina A. (Environment and Natural Resources Journal, 2025)
The potential utilization of 25 year old rubber tree (Hevea brasiliensis [Wild. ex A.Juss.] Müll. Arg.) clones (PB 260 and RRIM 600) were assessed based on their anatomical, physical, and mechanical properties. Anatomical features were evaluated using IAWA standards, while physical and mechanical properties were determined following ASTM D143-2019. Five trees per clone were collected from Naga, Zamboanga Sibugay. Results showed that PB 260 exhibited fiber dimensions significantly greater than RRIM 600, with 6.42% longer fibers, 9.42% larger fiber diameters, and 22.47% wider lumens. However, PB 260 had thinner cell walls by 13.33%. Vessel dimensions of PB 260 were also significantly higher, with 14.05% longer and 11.83% wider vessels. For physical properties, RRIM 600 showed higher basic relative density (0.53), tangential shrinkage (4.91%), and volumetric shrinkage (7.58%) compared to PB 260 (0.48, 4.52, and 7.21%, respectively). However, PB 260 had higher green moisture content (126.14%) than RRIM 600 (102.15%). Mechanical testing revealed RRIM 600 had higher strength, attributed to its higher basic relative density and thicker cell wall thickness. RRIM 600 is recommended for construction, flooring, and cabinetry, while PB 260 is suitable for medium grade furniture, carving, and pallets. The study highlights the potential of H. brasiliensis clones as alternative raw materials for the Philippine wood industry.